Evaluation of soybean meal, distillers dried grains with solubles, and the interactions among branched-chain amino acids in swine diets - Scher Cemin, Henrique (Kansas State University, 2019)
This dissertation consists of 8 chapters involving studies with branched-chain amino acids (BCAA), His requirements for nursery pigs, soybean meal (SBM) inclusion in nursery diets, and Zn source and level for grow-finish pigs. The first chapter presents a review of the literature on the interactions among branched-chain amino acids for growing pigs. Chapter 2 describes a meta-regression analysis conducted to develop prediction equations for growth performance based on BCAA, large neutral amino acids (LNAA), and their interactions. The results suggest that increasing Leu negatively impacts growth performance due to insufficient levels of other BCAA and LNAA relative to Leu. The addition of Val, Ile, and Trp, alone or in combination, has the potential to counteract the negative effects of high Leu. Chapter 3 describes two experiments that determined the His requirements of 7- to 11-kg nursery pigs. The results suggest that the His requirement is no more than 31% of Lys. Chapter 4 describes four experiments that evaluated the effects of increasing SBM in diets with or without distillers dried grains with solubles (DDGS). In general, DDGS reduced growth performance, although the magnitude was different across experiments. Increasing inclusions of SBM consistently improved G:F and caloric efficiency. Chapter 5 presents two experiments that estimated the energy value of SBM relative to corn. The results suggest that the energy value of SBM ranges from 105 and 125% of corn energy, which indicates that the NRC (2012) underestimates SBM energy. Chapter 6 describes a study that estimated the energy of high protein DDG for nursery pigs and found that it contains 97.3% of corn energy. Chapter 7 presents a Zn titration from 50 to 200 mg/kg for grow-finish pigs. There were no improvements in ADG beyond 50 mg/kg added Zn; however, providing 125 mg/kg added Zn resulted in the greatest G:F. Finally, chapter 8 evaluated Zn sources (Zn sulfate and Zn hydroxychloride) and levels (50 to 150 mg/kg) for grow-finish pigs. There were small improvements in ADG of pigs fed added Zn beyond 50 mg/kg. Zinc source did not influence growth performance, but Zn hydroxychloride improved carcass characteristics compared with Zn sulfate.
Keywords: Amino acids; Branched chain; Caloric efficiency; Soybean meal; Swine